Rectangular Microstrip Patch Antenna with Different Location of Minkowski Island Split Ring Resonator (MI-SRR) Structure - Hassan, Nornikman; Noor Azizi, Muhammad Syafiq; Ahmad, Badrul Hisham; Abd. Aziz, Mohamad Zoinol Abidin; Abu Bakar, Hamizan; Ramli, Mohamad Hafize; Othman, Mohd Azlishah; Sulaiman, Hamzah Asyrani (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this project, different locations of the Minkowski Island split ring resonator (MI-SRR) structure are embedded in the basic rectangular patch antenna. It started with a basic rectangular microstrip patch antenna that were simulated in CST Microwave Studio software. After that, four different locations (Location A, Location B, Location C and Location D) of MI-SRR were chosen to compare the performance of return loss, resonant frequency, surface current radiation pattern, and gain. Location A represented the antenna with the MI-SRR at the center part of the patch, while Location B had the MI-SRR at the upper part of the FR-4 substrate. Location C and Location D represented the antenna with MI-SRR at the ground at antenna with MI-SRR at the other layer, respectively. The return loss performances of Design of Location A, Location B, Location C, and Location D were - 26.546 dB, - 23.892 dB, -43.842 dB, - 51.506 dB at resonant frequency of 2.432 GHz, 2.510 GHz, 2.438 GHz and 2.542 GHz, respectively.